1984
DOI: 10.2527/jas1984.5961621x
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Endogenous and Exogenous Hormones for Red Meat Production

Abstract: SummaryGrowth and development of domestic livestock for red meat production are often discussed in the context of environmental factors, nutritional requirements, genetic potential and the anabolic agents affecting production efficiency. In this minireview, the effects of endogenous and exogenous hormones on animal growth are reviewed. The pituitary, pancreatic and gonadal hormones known to affect growth and(or) carcass composition are cited to illustrate and place into perspective the important contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Heitzman and Chan (1974) and Galbraith (1980) reported greater nitrogen retention and a decrease in plasma albumin in TBA-treated heifers. Schanbacher (1984) observed that immunizing intact males against estradiol increased rib-eye areas and fat thickness. In contrast, Wise and Ferrell (1984) observed no differences in water, fat or protein content between BSA-E and C heifers.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Heitzman and Chan (1974) and Galbraith (1980) reported greater nitrogen retention and a decrease in plasma albumin in TBA-treated heifers. Schanbacher (1984) observed that immunizing intact males against estradiol increased rib-eye areas and fat thickness. In contrast, Wise and Ferrell (1984) observed no differences in water, fat or protein content between BSA-E and C heifers.…”
Section: Resultsmentioning
confidence: 95%
“…Wise and Ferrell (1984) observed that BSA-E heifers had increased feed efficiency as compared with control heifers. Schanbacher (1984) reported that immunoneutralization provides a simple, non-invasive approach to endogenous hormone deprivation. Both active and passive immunization can be used to neutralize the activity of circulating hormones.…”
Section: Resultsmentioning
confidence: 99%
“…Although immunization against GnRH has proved to be partially effec¬ tive, there are problems relating to consistency and longevity of the immune response both within and between animals in most studies in the literature. An optimum dose of GnRH conjugate has not been deter¬ mined in farm animals; however, doses between 0.05 and 5.00 mg GnRH conjugated to various protein carriers have been shown to elicit immune responses with varying efficiency (Schanbacher, 1984a;Falvo et ah, 1986;Goubau et ah, 1989b;Lobley et ah, 1992;Adams and Adams, 1992). Carson et ah (1992) reported that 1.0 mg of a GnRH conjugate given to prepubertal bulls (n = 2) was more effective than 4.0 mg. An optimum primary-booster interval has not been determined in any of the studies carried out to date.…”
Section: Introductionmentioning
confidence: 97%
“…A study conducted by Schanbacher (1984) showed a 25.8% increase in ADG additionally Johnson et al (1996a) found an increase of 14-25% with the use of TBA-E 2 implants. In a different study, Johnson et al (1996b) showed an increase in carcass protein deposition with the use of TBA-E 2 .…”
Section: Carcass Effectsmentioning
confidence: 99%
“…However, reported that feeding ZH for 30 days resulted in loin eye muscle color that was a brighter cherry red color than the control. implanted steers when compared to non-implanted steers (Johnson et al, 1996a;Pampusch et al, 2008;Schanbacher, 1984). A combination of TBA, and E2 implants have been shown to amplify the observed effects including; feed efficiency, rate of gain, and muscle growth in cattle (Bruns et al, 2005;Eversole et al, 1989).…”
Section: Carcass Effectsmentioning
confidence: 99%